Charge transfer in and conductivity of molecularly doped thiophene‐based copolymers. Issue 1 (19th November 2014) - Ghani, Fatemeh; Opitz, Andreas; Pingel, Patrick; Heimel, Georg; Salzmann, Ingo; Frisch, Johannes; Neher, Dieter; Tsami, Argiri; Scherf, Ullrich; Koch, Norbert
ABSTRACT The electrical conductivity of organic semiconductors can be enhanced by orders of magnitude via doping with strong molecular electron acceptors or donors. Ground‐state integer charge transfer and charge‐transfer complex formation between organic semiconductors and molecular dopants have been suggested as the microscopic mechanisms causing these profound changes in electrical materials properties. Here, we study charge‐transfer interactions between the common molecular p‐dopant 2, 3, 5, 6‐tetrafluoro‐7, 7, 8, 8‐tetracyanoquinodimethane and a systematic series of thiophene‐based copolymers by a combination of spectroscopic techniques and electrical measurements. Subtle variations in chemical structure are seen to significantly impact the nature of the charge‐transfer species and the efficiency of the doping process, underlining the need for a more detailed understanding of the microscopic doping mechanism in organic semiconductors to reliably guide targeted chemical design. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2015, 53, 58–63